Efektifitas Penyederhanaan Partai Politik Era Orde Baru - Retanisa Rizqi (CV. Multi Kreasi Media, 2022)
The New Order is known as the era of renewal in the field of politics in Indonesia. Political parties are simplified for the sake of government stability. Of the many political parties in the Old Order, in the New Order they were simplified into three political parties that were allowed to exist, namely the Golkar Party, the United Development Party (PPP), and the Indonesian Democratic Party (PDI). This study discusses the effectiveness of the fusion of political parties in the New Order. The approach used is a qualitative method and the nature of this research is library research, analysis using interpretation and describing data with the intention of taking comparable values ​​in it and then drawing conclusions. The results obtained show that the simplification of political parties in the New Order was very effective in stabilizing economic problems, education to political problems. When viewed in terms of the process of simplifying political parties, it is an attempt by the new order regime which is juridically flawed. Efforts to perpetuate power by justifying all means to support the simplification of political parties are a juridical flaw.